An Ustilago maydis chassis for itaconic acid production without by‐products. Issue 2 (27th December 2019) - Becker, Johanna; Hosseinpour Tehrani, Hamed; Gauert, Marc; Mampel, Jörg; Blank, Lars M.; Wierckx, Nick
Summary: Ustilago maydis is a promising yeast for the production of a range of valuable metabolites, including itaconate, malate, glycolipids and triacylglycerols. However, wild‐type strains generally produce a potpourri of all of these metabolites, which hinders efficient production of single target chemicals. In this study, the diverse by‐product spectrum of U. maydis was reduced through strain engineering using CRISPR/Cas9 and FLP/FRT, greatly increasing the metabolic flux into the targeted itaconate biosynthesis pathway. With this strategy, a marker‐free chassis strain could be engineered, which produces itaconate from glucose with significantly enhanced titre, rate and yield. The lack of by‐product formation not only benefited itaconate production, it also increases the efficiency of downstream processing improving cell handling and product purity. Abstract : In this study, the diverse by‐product spectrum of U. maydis – including malate, glycolipids, and triacylglycerols – was reduced through strain engineering using CRISPR/Cas9 and FLP/FRT, greatly increasing the metabolic flux into the targeted itaconate biosynthesis pathway. With this strategy, a marker‐free chassis strain could be engineered which produces itaconate from glucose with significantly enhanced titre, rate, and yield. The lack of by‐product formation not only benefited itaconate production, it also increases the efficiency of downstream processing improving cell handling and product purity.